Limitaciones en el uso de corpus diacrónicos del español. Nuevas aportaciones desde el proyecto de investigación Post Scriptum - Vaamonde, Gael (2018)
The purpose of this paper is two-fold. On the one hand, some constraints on the computerized diachronic corpora currently available for Spanish research are explained. On the other hand, the Post Scriptum Project is presented, which aims to publish a collection of private letters written in Spanish and Portuguese along the Early Modern period. Post Scriptum can provide solutions to the shortcomings of other similar tools, making it a suitable resource for research in Historical Linguistics and an ideal complement to the existing large corpora.